The effect of work environment and emotional intelligence on affective commitment on millennial generation with job satisfaction as mediating variable - S, Dewi Winarni.; Malini, Helma; Daud, Ilzar; Shalahuddin, Ahmad; Sulistiowati, Sulistiowati (Enrichment : Journal of Management, 2023)
This study aims to analyze the influence of the work environment and emotional intelligence on affective commitment and job satisfaction as mediating variables among millennial employees in medium to large-scale industries in West Kalimantan. The study utilizes a descriptive quantitative research design with a sample of 200 millennial employees who participated in the survey via questionnaire. The sampling technique utilized the purposive sampling method, targeting employees working in the industrial sector in West Kalimantan, encompassing both contract and permanent employees from various divisions. A five-point Likert scale of 1 (Strongly disagree) to 5 (Strongly agree) was employed for data collection. In this study, the use of statistical software for measurement and analysis was conducted using Structural Equation Modelling (SEM) using AMOS 24. The findings indicate that the work environment and emotional intelligence positively and significantly impact job satisfaction. Additionally, both job satisfaction and the work environment positively and significantly impact affective commitment. Nevertheless, affective commitment is not significantly impacted by emotional intelligence.